ANALISIS METODE STORYTELLING DALAM KEMAMPUAN KOMUNIKASI ANAK USIA DINI - Widiana Wati; Maulida Nur; Vina Karina Putri; Yolanda Pahrul (STKIP Pesisir Selatan, 2026)
This study aims to analyze the implementation of the storytelling method in developing communication skills in early childhood at Miftahul Ulum Preschool. The background of this study stems from the discovery of several children experiencing communication barriers, such as difficulty expressing desires, lack of confidence, and minimal verbal interaction. This study used a qualitative approach with a case study type to gain an in-depth understanding of the storytelling implementation process and its impact on children's communication skills. The research subjects consisted of a class A teacher and two children aged 4–5 years who showed obstacles in language development. The results showed that the storytelling implementation was carried out through planned preparation, implementation, and closing stages. The teacher carefully prepared the theme, media, and delivery strategies to create an engaging learning experience. During the activity, the teacher used expressions, intonation, props, lead questions, and positive reinforcement to increase children's engagement. Observations revealed differences in communication skills between the two children. Child 1 showed developing verbal and nonverbal responses, while Child 2 was still passive and required additional stimulation.